Network Transformation from Local Geodetic System (Roma 40) to WGS 84, for an International Map of Geocentric Ellipsoid - Gargiulo, R.; Vassallo, A. (The International Hydrographic Review, 2018)
General algorithms are given to resolve the "GPS FIX", using vectorial procedures to transform coordinates from a local geodetic system to the WGS 84 system, with geodetic accuracy. The theory is based on the "invariance", in different geodetic systems, of the spatial distance or slope distance, that GPS receivers give with centimetric precision. The following method employs rectangular ellipsoidic coordinates (X,Y,Z) and their respective variations (ΔX,ΔY and ΔZ).